Adaptation of conventional and modern non-invasive methods for analysis of photoaged human skin barrier - Svoboda, Marek (Univerzita Pardubice, 2020)
This doctoral thesis deals with the phenomenon of unchanged or even decreased trans-epidermal water loss (TEWL) in the aged skin despite a decreased skin barrier lipids content. To address this task, analysis of structural components of the skin barrier was performed along with analysis of the skin barrier properties by using a wide range of methods. Optimal procedures for the skin sampling and subsequent sample handling and analysis were established as the first step. The second step included the analysis of the epidermal tight junction (TJ) proteins expression, lipid content and the skin barrier properties in the skin affected by ageing to select a potential target responsible for this phenomenon. The last part of this thesis challenged the target molecule occludin with regard to TEWL in the skin with diminished lipid barrier by using an ex vivo porcine skin model.
Adaptace konvenčních a moderních neinvazivních metod pro analýzu stárnoucí kožní bariéry
Keywords: imunochemie; konfokální mikroskopie; kožní bariéra; lipidy; PCR; tenko-vrstevná chromatografie; TEWL; těsné spoje; confocal microscopy; immunochemistry; lipids; PCR; skin barrier; thin-layer chromatography; TEWL; tight junctions